The effect of special exercises for some biomechanical variables of the rotation phase of 100 m freestyle for the swimmers of the national team (16-18 years old) - Yahya, Semaa; Abdul Rida, Bushra (Journal of Physical Education, 2025)
The aim of the research through study, analysis and clarifying the differences for the swimmers that the freestyle swimming style is preferred by most of the swimmers of the Iraqi national team, as the need for research and investigation has increased to solve the issues related to spinning performance and identify the values of some biomechanical variables of the spinning phase, swimming for 100 m freestyle swimming and the research issue lies due to the difficulty of directing swimmers during spinning performance in the water and the difficulty of communication between the coach and swimmers to give them accurate instructions during their spinning performance. The experimental method adopted the experimental design (pre-test, post-test for one group) to suit the nature of the research problem and the number of (6) swimmers representing 100% of the original population, which are the players of the Iraqi national team (16-18 years) and the experiment was conducted on the experimental group for (8) consecutive weeks at (3) times a week and after the completion of the application, the data were collected and the SPSS system processed the results to be the conclusions It is necessary to explain the importance of the biomechanical variables as indicated simply and to increase the culture and awareness of swimmers through the mediation and how the use of angles, distances, and appropriate force affects the economy of effort to create a developed sports generation to raise the level of sports for the better.